Կորստից փրկված մի ձեռագրի ոդիսականը - Ներսեսյան, Տեր Ներսես Ավագ Քահանա
According to the lengthy colophon this exceptional manuscript was copied at the church of St. Marina in Sis in 1222, by the scribe Yovhannēs, a pupil of the “incomparable” scribe Grigor Mlijets‘i. The existence of this manuscript was not known until today. The renowned scholar of miniature painting in the Kingdom of Cilicia Sirarpie Der Nersessian, in her investigation of Cambridge University Library MS. Add. 2620, also copied by Yovhannēs in 1217 at the church of St Marina expresses the view that the same scribe had copied a manuscript of the Four Gospels under the protection of the same church in 1222, formerly preserved in the church of the Holy Virgin Mary in Caesarea, but “lost and its existence is known only through an extract of the colophon.” The extract of the colophon is listed by Catholicos Garegin I Yovsepeants‘ and reprinted by Artashes Matevosian. With the exception of these two manuscripts dated 1217 and 1222 we have no further information on the scribe Yovhannēs. From the colophon of a manuscript of the Four Gospels dated 1173 we know of the careers of three scribes from the scriptorium of Skewra and Mlij. These were the priest Vardan († 1173), Kostandin nicknamed K. O. SH. I. K (1125-1195) and Grigor Mlijets‘i (or Skewrats‘i, c. 1150- 1215). Unfortunately, few of the illuminations have survived – the Letter of Eusebius to Carpianus, three of the Canon Tables and headpieces of the Four Gospels. The majority of the marginal decorations are ornamental with few motifs related to the text. The manuscript has been restored three times։ in 1293, 1496 and 1579. It was the property of the Church of the Holy Virgin Mary in Caesarea until 1886, when it was rescued and taken to Argentina. Согласно длинному колофону, эта уникальная рукопись была скопирована в церкви св. Марины в Сисе в 1222 г. Ованнесом, учеником «несравненного» писца Григора Млиджеци. О существовании рукописи по сей день не было известно. Видная исследовательница киликийской миниатюрной живописи Сирарпи Тер-Нерсесян в своем исследовании рукописи Add. 2620 из Кембриджской библиотеки, также скопированной писцом Ованнесом в 1217 г. в церкви св. Марины, выражает мнение о том, что тот же писец скопировал Четвероевангелие под сенью той же церкви в 1222 г.; ранее она хранилась в церкви св. Богородицы в Кесарии, но «была утеряна, и о ее существовании известно только благодаря отрывку из колофона». Этот отрывок упомянут в сборнике колофонов католикоса Гарегина I Овсепянца и перепечатан Арташесом Матевосяном. Кроме этих двух рукописей, датированных 1217 и 1222 годами, мы не рас- полагаем другой информацией о писце Ованнесе. Из колофона Четверо- евангелия 1173 года нам известно о деятельности трех писцов из скриптория в Скевре и Млиджа. Это – священник Вардан († 1173), Костандин по прозвищу Кошúк (1125-1195) и Григор Млиджеци (или Скевраци, ок. 1150-1215). К сожалению, сохранилось мало иллюстраций։ письмо Евсевия Карпиану, три канонические таблицы и заставки четырех евангелий. Большинство маргинальных украшений – это орнаменты и несколько относящихся к тексту сюжетов. Рукопись трижды реставрировалась։ в 1293, 1496 и 1579 гг. Она являлась собственностью церкви св. Богородицы в Кесарии до 1886 г., когда ее спасли и перевезли в Аргентину.
Keywords: Ձեռագրագիտություն